Re-assessment of "Claw-back" Clauses in the Enforcement of Human and Peoples’ Rights in Africa (Journal of Legal Studies, 2019)
One of the continuing problems, which had faced the African Charter, is many of its substantive provisions that are raven with qualifications without reasonable justification. These rights guaranteed under the Charter are subject to "claw-back" clauses that are introduced by governments and public authorities thereby undermining their citizen‟s basic constitutional rights of securing fundamental freedoms. They are those rights that impose negative duty on the state and are meant to promote the values of pluralism, equality and human dignity, which should be enjoyed free from state interference. It is in the interference of these rights that commentators have frequently criticized the African Charter for rendering its protective mandate meaningless and unenforceable. With hindsight, it is evident that the foregoing critique levelled against the "claw-back" clauses under Charter is justified, as they have a chilling effect on the exercise of human and peoples‟ rights on the African continent. Such condition has produced intense academic discussion on the interpretation and implications of the rights and freedoms enshrined in the Charter. None the less, the scope and the significance of the legal measures adopted by the African Commission have minimized the impact of the clauses affected considerably. Accordingly, a strong principle of interpretation adopted by the Commission has contributed to shaping the Charter‟s legal structure in harmony with international human rights law standards.